2019
DOI: 10.1177/1049909119849420
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Related Fatigue: Perception of Effort or Task Failure?

Abstract: Context: Patient’s rating of perceived effort (RPE) is used to assess central fatigue. Cancer-related fatigue (CRF) is believed to be of central origin. The increased RPE with a motor task, such as the Finger-Tapping Test (FTT), can easily be measured in the clinical setting. Objectives: To correlate the FTT, RPE and the Brief Fatigue Inventory (BFI) rated fatigue severity in patients with cancer. Methods: Subjective fatigue was assessed in adult patients with cancer by the BFI. Participants performed a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
10
2
Order By: Relevance
“…Potential disruptions originating in the central (inflammation, hypothalamic-pituitary-adrenal axis) and/or peripheral (e.g., reduced energy metabolism) nervous systems may induce CRF [ 44 •]. Central fatigue can be characterized as a perceived reduced ability to complete physical or mental tasks without demonstrable cognitive or motor deficiencies [ 55 , 56 ]. Peripheral fatigue is ascribed as the inability of muscles to perform a task in response to stimulation (“muscle fatigue”) or reduced endurance [ 44 •, 57 •].…”
Section: Mechanisms Underlying Crfmentioning
confidence: 99%
“…Potential disruptions originating in the central (inflammation, hypothalamic-pituitary-adrenal axis) and/or peripheral (e.g., reduced energy metabolism) nervous systems may induce CRF [ 44 •]. Central fatigue can be characterized as a perceived reduced ability to complete physical or mental tasks without demonstrable cognitive or motor deficiencies [ 55 , 56 ]. Peripheral fatigue is ascribed as the inability of muscles to perform a task in response to stimulation (“muscle fatigue”) or reduced endurance [ 44 •, 57 •].…”
Section: Mechanisms Underlying Crfmentioning
confidence: 99%
“…61 Once upon a time I spoke some remedial French and am currently learning Japanese 62 He also suggests utilising the definition provided by Marcora (2010); though, both I and others (Halperin and Emanuel, 2020) find this definition to include unnecessarily misleading terms. 63 Although, 'pain' has been reported as perceptually distinct from 'discomfort' during exercise (Hamilton et al, 1996) and so the latter may be preferable for such exercise induced perceptions unless injury itself has occurred. when this involves those whose language treats the words as such.…”
Section: Perception Of 'Exertion' or 'Effort'?mentioning
confidence: 99%
“…Pageaux (2016) has argued that, considering many within the literature do in fact use the two terms as synonyms already, and that many languages do the same, it may be best to instead use the terms interchangeably 62 . Instead, the descriptors of other phenomenological aspects associated with exercise (such as 'strain') might be better termed as 'pain' or 'discomfort' 63 . Following from this disagreement within the literature my research group has also been suggested a combined approach to the terminology should be used (Steele et al, 2017b).…”
Section: Perception Of 'Exertion' or 'Effort'?mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its omnipresence in our daily life, the interest in understanding perception of effort is growing amongst researchers. This perception is linked to the task intensity and the amount of resources invested (Inzlicht et al, 2018); strongly influences the self-regulation of human behaviour (Inzlicht et al, 2018;Marcora, 2015); is one of the main features of fatigue in various contexts (Enoka & Stuart, 1992;Pageaux & Lepers, 2016); and is exacerbated in various pathologies such as chronic fatigue syndrome (Barhorst et al, 2020;Cook et al, 2007), stroke (Kuppuswamy et al, 2015), chronic kidney disease (Macdonald et al, 2012) or cancer (Fernandez et al, 2020). Perception of effort is a fundamental experience that directly influences our everyday decisions to engage or disengage in various actions, by monitoring the cognitive and motor resources necessary to perform any task (Pageaux, 2016;Preston, 2009).…”
Section: Introductionmentioning
confidence: 99%